PERLINDUNGAN KONSUMEN ATAS INFORMASI YANG BENAR TERHADAP PROMOSI PRODUK DALAM TRANSAKSI PERDAGANGAN ELEKTRONIK MENURUT UNDANG–UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - evita lanosta; A.M Tri Anggraini (Jurnal Hukum Adigama, 2021)
The intense competition among business actors makes business actors compete to create business strategies to attract consumers. One of the strategies taken by business actors is to hold offers or promotions in various forms, including in the electronic commerce transaction. However, these promotions sometimes lead to promises that are not in accordance with the contents of the agreement given by the business actor. One of the cases of product promotion that misleads consumers is the case of PT. Vega Data Indonesia which has reached the court with the decision of the District Court No. 524 / Pis.Sus / 2020 / PN Jkt.Utr. How should the form of consumer protection for correct information on product promotion in electronic commerce transactions according to Law Number 8 of 1999 concerning Consumer Protection and other related regulations? Researchers examined these problems using normative legal research methods. Research data shows that there is a legal violation of the obligation of business actors to provide correct information on product promotion by business actors which results in consumers experiencing losses. The existing form of consumer legal protection includes two things, namely protection in the sense of prevention (preventive) and repressive legal protection (action). The form of preventive protection (prevention) is the guidance and supervision of consumers, while the form of repressive protection includes efforts to resolve disputes through channels (court) litigation and non litigation (out of court). Legal protection for consumers using online loan services by PT. Vega Data Indonesia is a form of repressive legal protection.